Meals described as healthy or unhealthy match public health education in England. (1st April 2015) - Laguna-Camacho, Antonio; Booth, David A.
Highlights: People's written reports of their eating episodes can be quantitatively studied Eating practices perceived as healthy and unhealthy differ in foods and contexts Public perception of healthy and unhealthy eating matches dietary guidance in England Dietary guidelines should go beyond food groups to habits that contribute to health Abstract: Dietary guidelines for the general public aim to lower the incidence of nutrition-related diseases by influencing habitual food choices. Yet little is known about how well the guidelines are matched by the actual practices that people regard as healthy or unhealthy. In the present study, British residents were asked in a cognitive interview to write a description of an occasion when either they ate in an unhealthy way or the eating was healthy. The reported foods and drinks, as well as sort of occasion, location, people present and time of day, were categorised by verbal and semantic similarities. The number of mentions of terms in each category was then contrasted between groups in exact probability tests. Perceived unhealthy and healthy eating occasions differed reliably in the sorts of foods and the contexts reported. There was also full agreement with the national guidelines on eating plenty of fruit and vegetables, eating small amounts of foods and drinks high in fat and/or sugar, drinking plenty of water, and cutting down on alcohol. There was a tendency to regard choices of bread, rice, potatoes, pasta and other starchy foods as healthy. Reported healthy and unhealthy eating did not differ in incidences of meat, fish, eggs, beans and other non-dairy sources of protein or of dairy foods and milk. These results indicate that operationally clear recommendations by health professionals are well understood in this culture but members of the public do not make clear distinctions in the case of foods that can be included in moderate amounts in a healthy diet.